2019
DOI: 10.1007/s40744-019-0165-3
|View full text |Cite
|
Sign up to set email alerts
|

Translating Improvements with Ixekizumab in Clinical Trial Outcomes into Clinical Practice: ASAS40, Pain, Fatigue, and Sleep in Ankylosing Spondylitis

Abstract: Introduction Ixekizumab, a humanized interleukin-17A antibody, has shown efficacy in ankylosing spondylitis (AS), with a greater proportion of ixekizumab-treated patients achieving an ASAS40 (Assessment of Spondyloarthritis International Society 40) endpoint compared to placebo. An ASAS40 response is a high standard that is not routinely used in clinical practice. The goals of this study were (a) to measure improvement in ixekizumab-treated patients in the four ASAS treatment response domains and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 23 publications
4
23
0
2
Order By: Relevance
“…In the current analysis of data from the COAST-X clinical trial of patients with nr-axSpA, we demonstrate that ixekizumab is effective at improving spinal PROs in patients with nr-axSpA. This analysis from COAST-X along with the previously reported results from COAST-V and COAST-W in r-axSpA indicate that treatment with ixekizumab is effective in improving the most impactful symptoms across the axSpA disease spectrum (r-axSpA and nr-axSpA) [15]. As previously reported in the r-axSpA trials assessing ixekizumab (COAST-V and COAST-W), here we also show that ASAS40 responders report greater improvements in PtGA, spinal pain, function, and stiffness, fatigue, and spinal pain at night compared with ASAS20 responders, and ASAS20 responders also report greater improvements in PROs than ASAS20 non-responders.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In the current analysis of data from the COAST-X clinical trial of patients with nr-axSpA, we demonstrate that ixekizumab is effective at improving spinal PROs in patients with nr-axSpA. This analysis from COAST-X along with the previously reported results from COAST-V and COAST-W in r-axSpA indicate that treatment with ixekizumab is effective in improving the most impactful symptoms across the axSpA disease spectrum (r-axSpA and nr-axSpA) [15]. As previously reported in the r-axSpA trials assessing ixekizumab (COAST-V and COAST-W), here we also show that ASAS40 responders report greater improvements in PtGA, spinal pain, function, and stiffness, fatigue, and spinal pain at night compared with ASAS20 responders, and ASAS20 responders also report greater improvements in PROs than ASAS20 non-responders.…”
Section: Discussionsupporting
confidence: 65%
“…The Assessment of Spondyloarthritis International Society (ASAS) responses, ASAS20 and ASAS40 (defined by criteria including improvements of 20% and 40%, respectively) and partial remission, are primary endpoints in axSpA randomized controlled trials (RCTs). While ASAS responses are valuable in the context of RCTs, physicians in clinical practice focus on individual patient symptoms, such as patient global disease activity (PtGA), spinal pain, function, stiffness, fatigue, and spinal pain at night [14,15]. The present study used data from the COAST-X trial to assess the impact of ixekizumab treatment over 52 weeks and explore how ASAS40 responses correlate with improvements in patient-reported outcomes (PROs).…”
Section: Introductionmentioning
confidence: 99%
“…As with previous findings, this meta-epidemiological study found that pain and PGA are important predictors for treatment responses in axSpA trials [79], thus emphasizing the value of reporting core domains separately.…”
Section: Discussionsupporting
confidence: 88%
“…For patients who do not respond to or tolerate NSAIDs, biological disease-modifying antirheumatic drugs (bDMARDs), mainly tumor necrosis factor inhibitors (TNFis), have been recommended since the early 2000s [4,5]. However, approximately 30 to 40% of patients have disease that remains active after standardized treatment with NSAIDs and/or bDMARDs [7][8][9]. The emergence of interleukin (IL)-17 inhibitors has changed the treatment landscape of active ankylosing spondylitis [10].…”
Section: Introductionmentioning
confidence: 99%